The Roman army between the Alps and the Adriatic - Horvat, Jana (Opera Instituti Archaeologici Sloveniae;Studia Alpium et Adriae, 2016)
The results of the international collaboration of the three institutions from Austria, Italy and Slovenia (Alpen-Adria-Universität Klagenfurt, Università degli studi di Udine and Znanstvenoraziskovalni center SAZU, Inštitut za arheologijo of Ljubljana) are being published in the Studia Alpium et Adriae series.New discoveries and the re-examination of old ones is offering new insights into the Roman army and the historical questions related to its presence and activity in the regions of the northern Adriatic and the eastern Alps. The first volume of Studia Alpium et Adriae contains the contributions of twenty-one authors from four countries (Italy, Slovenia, Croatia and Austria) who present the results of their work conducted in recent years within different research groups and projects.